Knowledge, attitudes and practices of professionals in pharmacy on hormonal contraception emergency (ECP) in Costa Rica - Barrientos Esquivel, Adrián; Vega Montoya, Alejandra; Marín, Carmen; Gómez Ramírez, Cristian (Población y Salud en Mesoamérica, 2012)
Unwanted pregnancy is worldwide a public health problem affecting many couples. In Costa Rica, although the prevalence of contraceptive use among women is 82,1%; the rate of unwanted pregnancy in the last child is 47%. To explore knowledge, attitudes and practices about emergency contraception a sample of pharmacy professionals were interviewed. Using a structured questionnaire, indications, side effects, mechanism of action, efficacy, availability to prescribe and actual prescription of emergency contraception pills were explored. Results show a high level of knowledge, existence and effects of ECP. Also low knowledge of its effectiveness and mechanism of action was found. Prescription reached only 10% of interviewed professionals. It is concluded that, despite the high level of knowledge, low prescription is related to low awareness of the existing evidence of its mechanism of action. Continuous update of current evidence about ECP mechanism of action is recommended